Study of the effect of excipients on the pharmacotechnological attributes of ribavirin capsules using the random balance method - Saliy, Olena; Bublyk, Andrii; Popova, Mariia; Fukleva, Larysa (Technologies and Engineering, 2025)
One of the main stages in the creation of solid pharmaceutical forms is pharmaceutical development, during which the quality, efficacy, and safety of the future drug are established. The selection of biopharmaceutical factors when planning technological research is a critical task in pharmaceutical development, complicated by the need for a comprehensive consideration of all influencing factors. The aim of this work was to investigate and analyse the impact of the quantitative characteristics of excipients on the quality indicators of powder masses and hard capsules containing ribavirin. Mathematical experimental planning was applied, enabling the creation of an optimal composition by identifying the relationships between factors and technological parameters that must ensure the pharmacological action of ribavirin. The random balance method was employed to select optimal excipients for inclusion in the composition of gelatin capsules. Based on the obtained statistical data, scatter diagrams were constructed, where the median magnitude indicated the significance of the factors’ influence on the corresponding quality characteristics. The study examined the effect of quantitative factors on the properties of capsule masses and hard capsules with ribavirin, manufactured using wet granulation. It was found that quantitative characteristics at both “high” and “low” levels did not demonstrate a significant effect on indicators such as “Bulk density”, “Tapped density” for capsule masses, and “Disintegration” for hard capsules. The greatest influence of excipients on the Hausner ratio (flowability) for powder masses and the uniformity of the capsule content mass was exerted by binding agents such as hydroxypropyl cellulose and povidone. Increased amounts of these binders improved these characteristics. Scatter diagrams showed that the loss in mass during the drying of capsule masses significantly improved with an increased amount of microcrystalline cellulose and a reduced content of crospovidone. Factors affecting the “Dissolution” parameter were identified, including an increased amount of croscarmellose sodium and a reduced content of magnesium stearate and povidone